Low-level laser therapy attenuates the acute inflammatory response induced by muscle traumatic injury. (3rd May 2016) - Silveira, Paulo Cesar Lock; Scheffer, Debora da Luz; Glaser, Viviane; Remor, Aline Pertile; Pinho, Ricardo Aurino; Aguiar Junior, Aderbal Silva; Latini, Alexandra
Abstract: The purpose of this work was to investigate the effect of early and long-term low-level laser therapy (LLLT) on oxidative stress and inflammatory biomarkers after acute-traumatic muscle injury in Wistar rats. Animals were randomly divided into the following four groups: control group (CG), muscle injury group (IG), CG + LLLT, and IG + LLLT: laser treatment with doses of 3 and 5 J/cm 2 . Muscle traumatic injury was induced by a single-impact blunt trauma in the rat gastrocnemius. Irradiation for 3 or 5 J/cm 2 was initiated 2, 12, and 24 h after muscle trauma induction, and the treatment was continued for five consecutive days. All the oxidant markers investigated. namely thiobarbituric acid-reactive substance, carbonyl, superoxide dismutase, glutathione peroxidase, and catalase, were increased as soon as 2 h after muscle injury and remained increased up to 24 h. These alterations were prevented by LLLT at a 3 J/cm 2 dose given 2 h after the trauma. Similarly, LLLT prevented the trauma-induced proinflammatory state characterized by IL-6 and IL-10. In parallel, trauma-induced reduction in BDNF and VEGF, vascular remodeling and fiber-proliferating markers, was prevented by laser irradiation. In order to test whether the preventive effect of LLLT was also reflected in muscle functionality, we tested the locomotor activity, by measuring distance traveled and the number of rearings in the open field test. LLLT was effective in recovering the normal locomotion, indicating that the irradiation induced biostimulatory effects that accelerated or resolved the acute inflammatory response as well as the oxidant state elicited by the muscle trauma.